How Multidimensional Approach of Entrepreneurial Orientation (EO) Effect Firm Performance: A Critical Review - Diandra, Didip; Azmy, Ahmad (Universitas Muhammadiyah Yogyakarta, 2021)
Research aims: This research aims to have a better understanding of relationship between EO and firm performance, a critical review of multidimensional approach to EO-firm performance is conducted in this paper.Design/Methodology/Approach: This is a qualitative research method which follow rigor of literature review and matrix review process from the selected papers. This paper aims to synthesize, evaluate the review, and then represent the dimension of EO on firm performance from multidimensional approach.Research findings: This study advances integrative framework to represent EO dimensions which explicates some pathways for entrepreneurs to implement EO on their business organization, else, in order to elevate sustainable growth. Also, this study concludes the most effective EO recipes for firm performance.Theoretical contribution/ Originality: This study does not only discuss the importance of EO in firm performance but also describe on how firms able to attain best performance in uncertain condition. The author stated innovativeness and competitive aggressiveness as the best EO recipes for enhancing firm performance.Practitioner/Policy implication: This study gives beneficial information to entrepreneurs about EO dimensions for enhancing firm performance.Research limitation/Implication: The study is limited to ten selected papers that confirms the application of EO dimensions on firm performance. Future research should explore more factors that explain EO-Firm relationship